Skating sprint performance and the influence of lower-body strength and power in professional and junior elite ice hockey athletes - Laakso, L. A.; Secomb, J. L. (Sports Biomechanics, 2023)
Skating sprint performance is essential for competitive success in ice hockey; however, it is unknown which component of a skating sprint is most critical for development throughout the performance pathway. Fifty-seven Swiss male ice hockey athletes were subjects (National League [NL], n = 22; Under 20 [U20], n = 20; Under 17 [U17], n = 15). Athletes performed: on-ice 30 m skating sprint, countermovement jump (CMJ), squat jump (SJ), and isometric mid-thigh pull (IMTP) tests in a single day. Linear mixed models, effect sizes and 95% confidence intervals were used to compare sprint performance and CMJ, SJ and IMTP between each performance level, with a correlation matrix used to determine the influence of lower-body strength and power on sprint performance. The NL and U20 athletes were significantly faster and had greater performance in most CMJ, SJ and IMTP variables compared to the U17 athletes, indicating minimum standards of lower-body strength and power are required to optimise technical performance. Significant differences were observed between NL and U20 for 10-20 m skating sprint split time and CMJ concentric relative peak and mean force, and reactive strength index-modified. Therefore, flying acceleration (10-20 m) is likely the most critical variable for pathway progression, with relative concentric force production the greatest influence.